Motivasi Disiplin Dan Kepuasan Kerja Pengaruhnya Terhadap Kinerja Karyawan - Hasyim, Wachid (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
This study aims to determine and analyze the effect of motivation on employee performance, this study also aims to determine and analyze the effect of discipline on employee performance, and aims to determine and analyze the effect of job satisfaction on employee performance. The type of research used is quantitative. With the population are employees of PT. Cakrawala Teknik Mandiri Indonesia with a total of 42 respondents. Data collection includes observation, distributing questionnaires and literature study. The analytical method used is the classical assumption test, validity test, reliability test, hypothesis testing and multiple linear regression test. The results of the research conducted concluded that partially the motivational variable had an effect on employee performance, the discipline variable had an effect on employee performance and the job satisfaction variable had an effect on employee performance. This is evidenced by the t-count value which is greater than the ttable value with a significant value below the value α.